One-Year Clinical Outcomes of the Legflow Drug-Coated Balloon for the Treatment of Femoropopliteal Occlusions Registry. (February 2019) - Stabile, Eugenio; Gerardi, Donato; Magliulo, Fabio; Zhelev, Drago; Chervenkoff, Vassil; Taeymans, Kim; Kotasov, Doncho; Goverde, Peter; Giugliano, Giuseppe; Trimarco, Bruno; Esposito, Giovanni
Purpose: To report the 1-year outcomes of the prospective Legflow drug-coated balloon (DCB) registry, which evaluated the safety and 12-month efficacy of the Legflow balloon in the treatment of femoropopliteal disease.Methods: The Legflow is a new generation of DCB that has a homogenous, stable surface coating incorporating 0.1-µm paclitaxel particles. From January 2014 to June 2016, 139 patients (mean age 67.1±10.8 years; 109 men) were enrolled at 4 European institutions. Seventy-nine (56.8%) patients had claudication, while 60 (43.2%) had critical limb ischemia (CLI). Mean lesion length (MLL) was 90.0±41.2 mm. Eighty (57.6%) patients were treated for de novo lesions (MLL 83.2±41.2 mm), 29 (20.9%) for postangioplasty restenosis (MLL 81.2±30.9 mm), and 30 (21.6%) for in-stent restenosis (MLL 117.0±39.5 mm). The primary outcome measure was freedom from binary restenosis as determined by a peak systolic velocity ratio ≥2.4 on duplex or >50% stenosis on digital subtraction angiography at 12 months. The secondary outcome was freedom from clinically-driven target lesion revascularization (CD-TLR) at 12 months.Results: Technical success was achieved in all the 139 treated patients. During the hospital stay, 3 CLI patients died of wound-related complications and 3 CLI patients underwent urgent TLR due to early occlusion in 2 and stent thrombosis in 1. At 12 months, 4 additional patients died of cardiac disease unrelated to the procedure. Of the 132 patients available for 1-year follow-up, the primary outcome (freedom from restenosis) was obtained in 107 (81.1%) patients. Freedom from CD-TLR was obtained in 110 (83.3%). Of the 25 late restenoses >50%, only 3 asymptomatic patients did not require TLR. Freedom from CD-TLR was higher in claudicants (87.0%) than in CLI patients (78.2%, p=0.20). In patients treated for in-stent restenosis, freedom from TLR at 1 year was 89.2%.Conclusion: These data suggest that the use of a new generation paclitaxel-coated balloon represents a safe and effective therapeutic strategy for femoropopliteal obstructions in different clinical and anatomical settings. These data will need to be confirmed with longer-term follow-up and in randomized controlled trials.